Dampak Sosial dan Ekonomi Pasar Pagi Kota Pangkapinang : Tinjauan Literatur dan Implikasi untuk Pengembangan Ekonomi Lokal - Aryansyah, Ary Fakturrachman; M. Afdal. S (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to assess the social and economic impact of Pasar Pagi Pangkalpinang on local economic development through a literature review and primary data obtained from interviews with traders and visitors. The market plays an important role as an economic and social hub, providing local employment opportunities as well as contributing to local government revenue through taxes and levies. The findings show that this market significantly increases traders' income and strengthens social cohesion within the community. However, government policies related to market relocation need to be further evaluated to ensure equitable benefits for all stakeholders. This study offers practical recommendations for improving market infrastructure and trader empowerment to promote sustainable local economic development.